The influence of cannabis smoke and cannabis vapour on simulated lung surfactant function under physiologically relevant conditions. (7th March 2019) - Davies, Michael J.; Birkett, Jason W.; Bolton, Hannah; Moore, Andrea
Abstract : The use of cannabis for medicinal/recreational purposes is widespread throughout the world. Smoke inhalation is known to cause airway irritation due to noxious substances (ie, benzene) within the mix. Thus, advanced vaporisation platforms (eg, Davinci IQ) have been developed to circumvent negative health implications. Here, we consider the impact that cannabis smoke and cannabis vapour have on simulated lung surfactant performance within a model pulmonary space (ie, 37°C, elevated humidity and related fluid hydrodynamics). In total, 50 mg of herbal material was ignited or placed within a Davinci IQ vaporiser with subsequent activation. The aliquots were collected and then analysed using gas chromatography‐mass spectroscopy for composition and cannabinoid (eg, Δ9‐tetrahydrocannabinol [Δ9‐THC]) concentration. The average content within cannabis smoke was 2.84% (0.07%, SD) Δ9‐THC, with the same for cannabis vapour being 0.88% (0.14%, SD). Aerosolised samples were transferred to the lung biosimulator. When compared with the pristine Curosurf system, challenge with cannabis smoke and cannabis vapour reduced the surface pressure term by 26% and 7% and increased film compressibility by 60% and 15% at 80% trough area, respectively. The net effect would be enhanced film elasticity and an increased work of breathing, being more pronounced on cannabis smoke inhalation. The trends noted were ascribed to two factors operating synergistically, namely the amount of Δ9‐THC (plus others) within the aerosolised samples and the associated toxicity profile. Further research is required to establish mass‐balance effects (ie, titrated outputs) along with detailed chemical profiling of material generated from the unrelated cannabis activation pathways.